Cinema as Testimony and Discourse for History: Film Cityscapes in Autobiographical Documentaries - Iván Villarmea Álvarez (Revue LISA)
Film images testify to the real appearance of the past, or at least its aesthetic, through old films or archival footage. However, the meaning of an image is never transparent but part of a cultural discourse to be interpreted. Therefore, cinema offers two possible historical readings: firstly as repository of authentic visual traces of the past, and secondly as representation that reveals the zeitgeist of a period. Classic documentaries tried to deal with historical issues in an objective way, but the evolution of the genre placed subjectivity at the centre of discourse. This paradigm shift explains why memory and identity are two of the main topics of post-modern documentaries, such as some “urban autobiographies” that recall the emotional experience of missing cityscapes: Roger and Me (Michael Moore, USA, 1989), My Winnipeg (Guy Maddin, Canada, 2007) and Of Time and the City (Terence Davies, UK, 2008). These films share a similar subjective approach to portraying the decline of industrial towns through personal memories, despite their belonging to three different subgenres: the performative political documentary, the essay film and the self-fiction. The analysis of their formal devices can be very useful to reflect on our contemporary systems of historical representation.